Video Games as Language Learning Tools - Hladonik Gergely; Гладоник Гергель (Видавничий дім «Гельветика», 2021)
Abstract. Learning a language is focused around the traditional teaching process where students sit in the classroom to acquire knowledge. Basically, learning is concentrated on the teacher-student interaction. However, in the last decades, video games have been gaining popularity not only for enjoyment but also as an object of interest in academic research. However, the potential of video games for teaching has not been researched in much detail. Existing research into video games for learning has largely been based on theoretical ideas instead of looking into practical issues. Moreover, there is considerably less research into using video games as a form of language learning method. Their potential has been discussed but again, practical research is scarce. Over the past few decades, video games have become important part of children’s play and adult’s leisure time. The technology has developed far enough to be compared to films and animations in their capacity to tell a fascinating story, to be well presented and directed. Video games have two important advantages over these mediums: interactivity and the form of communication. Communication is especially important in increasing the proficiency of a non-native English speaker. Playing the right games may help children to learn a lot and improve their thinking skills. According to their content, video games can be divided into: action games, adventure games, casual games, simulation games, strategy games, sport games, edutainment games. The aim of this study is to investigate the impact of using video games on English language learners. Playing video games is a complex activity that stimulates senses, includes strategic thinking and develops motivation for learn ing. Gamers think, analyse and plan to achieve goals. As an education tool, video games are fun, simple, adaptive and rewarding. The use of video games serve as an alternative way of learning that permits learners to engage in dynamic activities that allow learning and enjoy ing at the same time, increasing motivation. As a form of highly desirable entertainment, video games provide a positive and motivating atmosphere, which is perfect for adopting a foreign language.

Резюме. З появою інформаційних технологій та винаходом комп’ютерів для людства відкрилися нові можливості в різних сферах життя (повсякденному, науковому житті, розвагах тощо). Відеоігри не завжди слугували інструментом для вивчення мови. До 1980-х років на чорно-білому екрані не з’являлося нічого, крім декількох фігур. Однак із часом відеоігри стають дедалі складнішими, створюючи можливості для впровадження та розвитку спочатку пасивних, а потім активних мовних навичок. Відеоігри як можливість вивчення мови потрапили в центр уваги лише в останнє десятиліття. Багато людей намагалися надати визначення відеоігор, із цих визначень зрозуміло, що відеоігри виконують безліч функцій. Згідно з дослідженням Дж. Джуула, відеоігри базуються на правилах, що забезпечують для гравців більше можливих варіантів реалізації виконання. Під час гри останні емоційно прив’язуються до неї, до самого процесу гри. Дж. Туров класифікує відеоігри на декілька груп залежно від їх функцій: «екшн»-ігри, імітаційні ігри, спортивні ігри тощо. Самі відеоігри мають розділи введення та виходу, які фокусуються на гравці. Ігри побудовані таким чином, що правила, місії та завдання повинні бути виконані, унаслідок чого рівень задоволеності гравця грою зростає. Якщо відеоігри правильно структуровані, вони також можуть бути використані як інструмент вивчення мови, а для вчителів буде доступний новий навчальний засіб. Під час гри у студента можна розвинути декілька здібностей, зокрема соціальні та пізнавальні. Вибірка для дослідження була обрана випадковим способом. Учасники отримали за посиланням анкету, яка складалася з 9 запитань. Перша половина запитань стосувалася загальної інформації, а наступні запитання – звичок учасників у відеоіграх. Наостанок були запитання, які вивчали навички, що використовуються у відеоіграх. Результати чітко показують, що респонденти грають у відеоігри, проте віддають перевагу такому виду відпочинку не лише для проведення вільного часу, а й для вивчення мови. Результати також показують, які популярні типи гри покращують мовні навички гравців. Ігри, у яких використовується певний рівень спілкування, мають перевагу над іншими типами ігор.
Відеоігри як засоби вивчення мови
Keywords: computer games; video games; gamification; language learning